Guiding a steamboat using ropes through Five Finger Rapids on the Yukon River, Yukon Territory, approximately 1899. - Hegg, Eric A., 1867-1948 (1899)
Caption on image: "Roping a steamer through Five Finger Rapids". Klondike Gold Rush.